A study of the financial effects of Lenovo's acquisition over IBM PC business. - Lim, Hui Hoon. (2008)
Purports Merger and Acquisition (M&A) is increasingly becoming an important vehicle for expansion as the global trend of cross-border M&A is on the rise. It is under this backdrop that we examine the effects of Lenovo’s cross-border acquisition over IBM PC Business on Lenovo’s financial performance. We investigate Lenovo’s short-term stock performance, as well as long-term operating and stock performance. Our short and long run analyses show that Lenovo experiences an overall unfavorable financial performance after the initial announcement of the acquisition. In addition, our long run operating performance analysis reveals that Lenovo has underperformed relative to the benchmarked firms. Hence, Lenovo’s cross-border acquisition of IBM PC Business may not be reaping as much benefits as what Lenovo’s management initially set out to be. Thus, there is a need for more deliberate and careful planning should such similar type of acquisition for global expansion is to be again undertaken by Lenovo’s management.